The problem of lesser evil within the context of public health - Sytnik-Czetwertyński, Janusz; Cianciara, Dorota (Journal of Education, Health and Sport, 2016)
Sytnik-Czetwertyński Janusz, Cianciara Dorota. The problem of lesser evil within the context of public health. Journal of Education, Health and Sport. 2016;6(10):299-308. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.162532 http://ojs.ukw.edu.pl/index.php/johs/article/view/3947 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 02.10.2016. Accepted: 20.10.2016. The problem of lesser evil within the context of public health Janusz Sytnik-Czetwertyński UKW w Bydgoszczy, Poland Dorota Cianciara Szkoła Zdrowia Publicznego w Warszawie, Poland Abstract The issue of public health also includes broad ethical questions. It is here for instance that we find so-called decisions of conscience. Since medical practice is full of moral dilemmas, transferred into the domain of public health, for instance when a doctor decides to provide, in individual cases, costly medical procedures while being simultaneously aware that the funds used for these procedures, could save many more people whose ailments are less costly. These situations force the medical practitioner into making a decision, despite the fact that all the possible choices are morally reprehensible . There exist many moral dilemmas, where the person making the decision cannot find a satisfactory solution, while also being forced to make a decision. Normally, the decision maker then calls upon the category of so-called lesser evil. But this category is no justification – lesser evil is still evil. Which is why it is worth asking what the situation of lesser evil is for the decision maker . What is a moral choice within a public health policy? Key words: public health, the ethical dilemma, naturalism